2021
DOI: 10.1007/s10802-021-00798-w
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Friendship Difficulties in the Pathway from ADHD to Depressive Symptoms. Can Parent–Child Relationships Compensate?

Abstract: Attention deficit/hyperactivity disorder (ADHD) is associated with friendship difficulties. This may partly account for the increasingly recognised association between ADHD and subsequent depression. Little is known about the types of friendship difficulties that could contribute to the association between ADHD and depressive symptoms and whether other relationships, such as parent–child relationships, can mitigate against potential adverse effects of friendship difficulties. In a representative UK school samp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 76 publications
0
6
0
1
Order By: Relevance
“…However, the notion that psychosocial problems associated with ADHD increase the risk of negative mental health outcomes in people with ADHD is gaining popularity (Roy et al, 2015 ; Schatz & Rostain, 2006 ; Simmons & Antshel, 2020 ). This theory suggests that ADHD creates a more negative environment, characterized by experiences of failure, rejection, and stress, that makes it more difficult for people with ADHD to flourish and manage their mental health (Powell et al, 2020 , 2021 ; Roy et al, 2015 ; Schatz & Rostain, 2006 ; Simmons & Antshel, 2020 ). Other emerging evidence suggests that self‐compassion may be particularly important for the mental health of adults with ADHD (Geurts et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the notion that psychosocial problems associated with ADHD increase the risk of negative mental health outcomes in people with ADHD is gaining popularity (Roy et al, 2015 ; Schatz & Rostain, 2006 ; Simmons & Antshel, 2020 ). This theory suggests that ADHD creates a more negative environment, characterized by experiences of failure, rejection, and stress, that makes it more difficult for people with ADHD to flourish and manage their mental health (Powell et al, 2020 , 2021 ; Roy et al, 2015 ; Schatz & Rostain, 2006 ; Simmons & Antshel, 2020 ). Other emerging evidence suggests that self‐compassion may be particularly important for the mental health of adults with ADHD (Geurts et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Given the protective value of self‐compassion, it is particularly important to assess self‐compassion in people with ADHD because they are likely to experience more negative events (Asherson et al, 2018 ) and more stressful daily and life events that negatively impact mental health (Friedrichs et al, 2012 ; Skirrow et al, 2014 ). For example, ADHD is associated with poor academic outcomes (Loe & Feldman, 2007 ), impaired relationships (Murphy & Barkley, 1996 ), and increased stigma, criticism, and rejection (Canu et al, 2008 ; Hoza, 2007 ; Psychogiou et al, 2007 ), and each of these factors have been shown to explain the link between ADHD and levels of depression (Powell et al, 2020 , 2021 ; Simmons & Antshel, 2020 ). In neurotypical populations, self‐compassion has been shown to buffer the negative emotional consequences of academic failures (Neff et al, 2005 ), relationship issues (Sbarra et al, 2012 ; Yarnell & Neff, 2013 ), and stigma/criticism (Neff & Faso, 2015 ; Vigna et al, 2018 ; Wong et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of the studies indicated that there is an observed consistency in the findings across all but two cross-sectional studies which suggests a beneficial association between better peer relationship and depressive symptomology during adolescence, but this consistency was not observed in the results of the six longitudinal studies as they varied in their conclusions. Of these six studies, two methodologically-sound studies supported the evidence of presence of a beneficial association between better peer bonds and lower depressive symptoms [83,86,94]. On the other hand, one short-term study demonstrates null effect of peer relationships on depressive symptoms [85].…”
Section: Friendship Quality and Depressive Symptomsmentioning
confidence: 84%
“…One study, however, did not find strong evidence of mediation by declining best-friend relationship quality across adolescence (Meinzer et al, 2020). Depression in ADHD and ASD Interestingly, Powell, Riglin, et al (2021) found evidence that the association between ADHD and depression symptomsmediated via friendship qualityattenuated in children with more positive parent-child relationships. This highlights that positive social relationships in one context may be able to compensate for poor social relationships in others.…”
Section: Social-environmental Mechanismsmentioning
confidence: 95%
“…Peer relationships also are implicated. Population‐based studies have observed that friendship quality and peer problems (Powell, Riglin, et al., 2021 ), and being victimised by peers (Roy, Hartman, Veenstra, & Oldehinkel, 2015 ), partially mediate the association between ADHD and depression symptoms. One study, however, did not find strong evidence of mediation by declining best‐friend relationship quality across adolescence (Meinzer et al., 2020 ).…”
Section: Why Are Young People With Adhd / ...mentioning
confidence: 99%